2007
DOI: 10.1177/10442073070180030401
|View full text |Cite
|
Sign up to set email alerts
|

High-Stakes Testing and Students With Disabilities

Abstract: The use of high-stakes testing has become an increasingly popular assessment for schools to use in demonstrating individual academic performance of students, and providingaccountability for school improvement. Given the potential negative consequences associated with mandatory testing (e.g., grade retention, withholding of high school diplomas, labeling failing schools), students, parents, and school districts all bear significant risks based upon student test scores. The historically poor performance of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…While these concerns have been raised, more recent reviews of high-stakes testing and increased emphasis of accountability indicate many positive outcomes (Katsiyannis et al, 2007). Hager and Slocum (2011) have indicated that carefully designed alternate assessment systems have the potential to provide meaningful information about the progress of all students, including those with significant cognitive disabilities, that can guide decisionmaking at the classroom and district level.…”
Section: Improving Access To Naplan For All Students: Lessons From Abmentioning
confidence: 99%
“…While these concerns have been raised, more recent reviews of high-stakes testing and increased emphasis of accountability indicate many positive outcomes (Katsiyannis et al, 2007). Hager and Slocum (2011) have indicated that carefully designed alternate assessment systems have the potential to provide meaningful information about the progress of all students, including those with significant cognitive disabilities, that can guide decisionmaking at the classroom and district level.…”
Section: Improving Access To Naplan For All Students: Lessons From Abmentioning
confidence: 99%
“…Special needs students have much in common with many other segments of the school population who are disadvantaged in terms of academic achievement (Katsiyannis, Zhang, Ryan & Jones, 2007;O'Donnell, & White, 2005;Dantley & Tillman, 2006), cultural inclusion within the norms and values of a "mainstream" school population and curriculum (Delpit, 1988;Marshall & Oliva, 2006;Cooper, 2009;Brooks, Jean-Marie, Normore, & Hodgkins, 2007;and Riehl, 2000) and effective leadership for their distinct needs (Theoharis, 2007;Theoharis & Causton-Theoharis, 2008). Advancing democratic ideals for all students is fundamental to the vision of a just society as Dewey (1916) so convincingly articulated.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…School leaders are expected to produce high levels of student achievement and schools have placed special needs students into separate programs which have been inadequate in serving their academic needs and have marginalized them from the rest of the student population (Katsiyannis, Zhang, Ryan, & Jones, 2007;McKenzie et al, 2008;Solórozano, 2008). Despite this trend, transformative leaders have successfully challenged traditional school systems through such practices as inclusion and, in doing so better serving special needs students (Brooks, Jean-Marie, Normore & Hodgkins, 2007;Theoharis, 2007;Theoharis & Causton-Theoharis, 2008).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, after a literature review on high-stakes testing in light of NCLB, Katsiyannis, Zhang, Ryan and Jones (2007) concluded that high stakes testing increased: (a) participation of SWD in formal state assessments, (b) levels of performance by special education students in high-stakes testing, and (c) participation of special educators in training on standards and assessments. Negative consequences in high-stakes testing, per Katsiyannis et.…”
Section: Students With Disabilities and High Stakes Testingmentioning
confidence: 99%